Aesthetic and functional rehabilitation in a patient with gastroesophageal compromise and temporomandibular disorder: a case report - Campaner, Marcio (2021)
A 32-year-old male patient attended in the Fixed Partial Prosthesis Clinic (PPF), of the Araçatuba Dental School-Paulista State University, stating as the main complaint that his anterior teeth were “ugly and broken”. After clinical examination, the patient was diagnosed with temporomandibular disorder, bruxism and the presence of dental erosions (intrinsic and extrinsic). It was proposed to be followed up by a gastroenterologist and rehabilitation with metal-free prostheses (11, 12, 21 and 22) made of lithium silicate reinforced with zirconium by the CAD / CAM system were proposed. After endodontics of the anterior-superior incisors, the anatomized fiberglass posts with composite resin were installed; the impression was made with retractor wire and addition silicone. After aesthetic testing and occlusal adjustments, the e-max Ceram PPF¨s were prepared for resin cementation with the Variolink II color Light system. After 1 week, the impression of the upper arch was taken and subsequently a muscle relaxant plate was installed. The patient and the professionals involved approved the final result, verifying the aesthetic efficacy associated with the use of a metal-free prosthesis, despite the fact that the patient has gastroesophageal involvement and temporomandibular disorder.